Implementasi Renstra Kantor Wilayah Kementerian Agama Provinsi Banten Bidang Madrasah Tahun 2020-2024 Dalam Meningkatkan Kualitas Guru - Husni Abdul Azizi; Anis Fauzi; Agus Gunawan (Departement of Mathematics Education, 2023)
The teacher is the spearhead of educational progress, if the teacher has good competence, it is certain that the output produced will also be good. But in reality this is not always the case, the problem of student delinquency which is still a scourge in the world of education suggests that the role of the teacher so far has only been limited to teaching material in class, moreover the teacher is considered weak because he has not been able to transform the essential values ​​of education as a whole. in the learning process. In order for the implementation of education to be more focused, a policy is needed which is the basic reference as well as a legal umbrella to overcome problems in the world of education. The policies that have been set are expected to be able to improve the quality of existing education. The formulation of the problem of this thesis is how is the policy of the Regional Office of the Ministry of Religion of Banten Province in improving the quality of teachers, how is the implementation of the strategic plan of the Regional Office of the Ministry of Religion of Banten Province in increasing teacher competence, how is the monitoring and evaluation system of the Regional Office of the Ministry of Religion of Banten Province in improving teacher quality, what is only the obstacles that impede the improvement of teacher quality in the Regional Office of the Ministry of Religion of Banten Province. This research is a qualitative research. The subjects of this study were the Head of the Madrasah Education Section of the Ministry of Religion of Banten Province and the Madrasa Supervisors. The place of research was conducted at the Regional Office of the Ministry of Religion of Banten Province. The method of collecting data using interview techniques, observation and documentation. The results of the study show that: the policy of the Banten Province Ministry of Religion in improving teacher competence is to refer to Law no. 14 of 2005 concerning Teachers and Lecturers whose main focus is related to the teacher certification program which includes four competencies, namely pedagogic competence, social competence, professional competence and personality competence. Implementation of the strategic plan of the Ministry of Religion of Banten Province in improving teacher quality in collaboration with the Madrasah Head, Subject Teacher Consultation (MGMP), Teacher Performance Group (KKG) is used as a medium to socialize programs that will be and are being implemented and involve teachers in training, training and seminar. The supervision and evaluation system of the Ministry of Religion of Banten Province in improving teacher competence is by implementing a monitoring and evaluation system that is formative, summative and progress carried out monthly, semiannually and annually. There are two main obstacles faced in implementing existing policies, first, the problem of inadequate budget funds. Second, related to the lack of motivation and internal awareness of teachers to continue to develop their competence.